LABORATORY EXAMINATION OF HEMOLYTIC DISEASE IN NEONATES DUE TO RHESUS INCOMPATIBILITY - Danny Ernest Jonas Luhulima,; Christian Ronald Tanggo,; Ria Amelia, (Journal of Innovation Research and Knowledge, 2026)
Hemolytic disease of the newborn (HDN) occurs when fetal red blood cells (RBCs), which possess an antigen that the mother lacks, cross the placenta into the maternal circulation, where they stimulate antibody production. The antibodies return to the fetal circulation and result in RBC destruction. Three classifications of HDN are: ABO, other causes like unexpected immune antibodies like anti-c or anti-K and Rhesus–anti D alone or may be accompanied by other Rh antibodies, examples anti-D with anti-C or anti-E. Clinical presentation of HDN varies from mild jaundice and anemia to hydrops fetalis (with ascites, pleural and pericardial effusions). This article discusses hemolytic due to incompability Rhesus anti-D.)